Metastatic Phaeochromocytoma: Spinning Towards More Promising Treatment Options - Nölting, Svenja; Grossman, Ashley; Pacak, Karel (Experimental and Clinical Endocrinology & Diabetes, 2019)
Phaeochromocytomas (PCC) and paragangliomas (PGL) are rare tumours arising from the chromaffin cells of the adrenal medulla (PCC) or the paraganglia located outside the adrenal gland (PGL). However, their incidence is likely to be underestimated; around 10% of all PCC/PGL are metastatic, with higher metastatic potential of PGLs compared to PCCs. If benign, surgery is the treatment of choice, but if metastatic, therapy is challenging. Here we review the currently existing therapy options for metastatic PCCs/PGLs including conventional chemotherapy (the original Averbuch scheme, but updated), radiopharmaceutical treatments (131I-MIBG, 90Y- and 177Lu-DOTATATE) and novel targeted therapies (anti-angiogenic tyrosine kinase inhibitors and mTORC1 inhibitors), emphasising future therapeutic approaches (HIF-2α and PARP inhibitors, temozolomide alone, metronomic temozolomide, somatostatin analogues) based on the oncogenic signalling pathways related to three different clusters comprising more than 20 well-characterised PCC/PGL susceptibility genes. We suggest that targeted combination therapies including repurposed agents may offer more effective future options worthy of exploration.
Keywords: Malignant phaeochromocytoma; therapy; oncogenic signalling